2004
DOI: 10.1007/s10147-005-0475-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for metastatic malignancies. Anatomical resection of liver metastasis: indications and outcomes

Abstract: Hepatectomy may be the only treatment modality for the cure of colorectal liver metastasis. However, whether to perform nonanatomical resection or anatomical resection remains unclear. Original articles in English on liver metastasis, including reports that dealt with case series of more than 50 curative hepatectomies, were reviewed, and the current status of surgical treatment for colorectal liver metastasis was summarized, with a special emphasis on the relevance, indications, and outcomes of anatomical hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 129 publications
(217 reference statements)
2
29
1
4
Order By: Relevance
“…4,5 Although some studies have reported that the performance of an anatomical resection improves tumor clearance and outcome, other reports have not demonstrated a benefit for anatomic or ''extended'' resections. 4,6 In general, most surgeons have begun to advocate a more parenchymalsparing approach to resection of hepatobiliary tumors that still maintains a negative margin. In support of this, our group previously reported that the extent of hepatectomy for gallbladder carcinoma was not associated with prognosis.…”
mentioning
confidence: 99%
“…4,5 Although some studies have reported that the performance of an anatomical resection improves tumor clearance and outcome, other reports have not demonstrated a benefit for anatomic or ''extended'' resections. 4,6 In general, most surgeons have begun to advocate a more parenchymalsparing approach to resection of hepatobiliary tumors that still maintains a negative margin. In support of this, our group previously reported that the extent of hepatectomy for gallbladder carcinoma was not associated with prognosis.…”
mentioning
confidence: 99%
“…Simple cholecystectomy is sufficient for T 1A GBC (2), and 5-year survival rate has been reported to be 90-100% for these tumors (20). Two out of the 3 patients graded as in situ cancers in our study are still alive.…”
Section: Discussionmentioning
confidence: 55%
“…Algunos autores proponen realizar resecciones locales o no anatómicas 23 y otros, realizar resecciones hepáticas anatómicas 24 . Existen pocos trabajos que comparen ambas técnicas en forma adecuada 25 .…”
Section: Discussionunclassified
“…Las resecciones anatómicas tendrían los beneficios de lograr un mejor margen y que pueden incluir metástasis en la pieza quirúrgica no pesquisadas previamente, con una morbilidad similar. El sangrado quirúrgico es más controlado, debido a que se siguen planos anató-micos en la transección hepática 24 . Las resecciones no anatómicas permiten preservar una mayor cantidad de parénquima hepático sano, lo que es de especial relevancia en pacientes con fibrosis o esteatosis hepática mayor.…”
Section: Discussionunclassified